Wages or Fringes? Some Evidence on Trade-Offs and Sorting - Eriksson, Tor; Kristensen, Nicolai (Journal of Labor Economics, 2014)
The two key predictions of hedonic wage theory are that there is a trade-off between wages and nonmonetary rewards and that the latter can be used as a sorting device by firms to attract and retain the kind of employees they desire. We use the vignettes method to estimate individuals’ willingness-to-pay for fringe benefits and job amenities. We find negative wage-fringe trade-offs, considerable heterogeneity in willingness-to-pay for fringe benefits, and signs of sorting.